Understanding ethnic segregation in contemporary Britain - Halsall, Jamie (European economic and political issues series., 2013)
The population of ethnic minorities in Britain has rapidly increased over the last 60 years. The census count indicates that the ethnic population has grown from 3 million in 1991 to 4.6 million in 2001. Issues surrounding ethnic minorities have duly been concerned with education, employment and housing. In 2001, civil unrest erupted in England's northern mill towns. The inquiries concluded that white and British Asian communities were living parallel lives. This was seen to be a failure within the communities and of social policy. Segregation was cited as a contributory factor. Moreover, in 2.